Detecting Authoritarianism Efficiently: Psychometric Properties of the Screening Instrument Authoritarianism – Ultra Short (A-US) in a German Representative Sample - Heller, Ayline; Decker, Oliver; Schmalbach, Bjarne; Beutel, Manfred; Fegert, Jörg M.; Brähler, Elmar; Zenger, Markus (Frontiers in Psychology, 2020)
With right-wing-extremist and -populist parties and movements on the rise throughout the world, the concept of authoritarianism has proven to be particularly valuable to explain the psychological underpinnings of these tendencies. Even though many scales to measure the different dimensions of authoritarianism exist, no short screening instrument has been tested and validated on a large scale so far. The present study examines the psychometric properties of the screening instrument Authoritarianism – Ultrashort (A-US) in three representative German samples (n= 2,524, n= 2,478, and n = 2,495). Using exploratory and confirmatory factor analysis, the A-US demonstrated acceptable internal consistency. Model fit was good and correlations with related constructs indicated convergent validity in both samples. Construct validity was demonstrated using the original version of the scale. The instrument proved to be invariant across sex, employment status and education, but not across different age groups. Finally, the analyses showed that differences in the A-US are associated with sociodemographic variables. Potential causes and effects of these findings are discussed. Based on these results, the A-US proved to be a valuable and highly efficient tool to screen for authoritarian tendencies.